2007
DOI: 10.1007/s12237-007-9006-7
|View full text |Cite
|
Sign up to set email alerts
|

Foraging by Two Estuarine Fishes, Fundulus heteroclitus and Fundulus majalis, on Juvenile Asian Shore Crabs (Hemigrapsus sanguineus) in Western Long Island Sound

Abstract: The Asian shore crab, Hemigrapsus sanguineus,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, while they have fewer parasites, they are more susceptible to infection 46 , and parasite load appears to be increasing since the initial escape from parasites at introduction, as native parasites in the invaded range expand to include this new host 47 . Similarly, while predation and competition have played a minor role in limiting the early invasion of this species 28,40,[42][43][44] , it is possible that these processes may be taking on a greater role as time progresses, if native species learn to consume Asian shore crabs or more effectively interact with them. Thus, while our study does not suggest that resource limitation is the only, or even the predominant, mechanism leading to the decline of Asian shore crab populations, our results certainly do point to self-limitation because of food depletion as a contributing mechanism in the decline of this widespread invader.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while they have fewer parasites, they are more susceptible to infection 46 , and parasite load appears to be increasing since the initial escape from parasites at introduction, as native parasites in the invaded range expand to include this new host 47 . Similarly, while predation and competition have played a minor role in limiting the early invasion of this species 28,40,[42][43][44] , it is possible that these processes may be taking on a greater role as time progresses, if native species learn to consume Asian shore crabs or more effectively interact with them. Thus, while our study does not suggest that resource limitation is the only, or even the predominant, mechanism leading to the decline of Asian shore crab populations, our results certainly do point to self-limitation because of food depletion as a contributing mechanism in the decline of this widespread invader.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous work suggests that these mechanisms may have relatively little impact on Asian shore crabs in their invaded range. For instance, existing evidence suggests that common potential predators do not heavily prey on Asian shore crabs [42][43][44] . Additionally, competition does not seem to play a major role, as this species has the upper hand in interspecific interactions with other intertidal crabs 28,40 and displays fairly weak conspecific interference competition 45 .…”
mentioning
confidence: 99%
“…Arthropoda O Consumption Parasitism Enhanced (Blakeslee et al 2009) Hemigrapsus sanguineus Arthropoda O Consumption Predation Enhanced (Brousseau et al 2008) Hemigrapsus sanguineus Arthropoda E Consumption Predation Limited (Heinonen & Auster 2012) Hemigrapsus sanguineus Arthropoda E Competition Single-Species Competition Enhanced (Jensen et al 2002) Hemigrapsus sanguineus Arthropoda E Competition Single-Species Competition Enhanced (Landschoff et al 2013) Hemigrapsus sanguineus Arthropoda E Competition Single-Species Competition Enhanced (Lohrer & Whitlatch 2002) Hemigrapsus (Mumby et al 2011) Pyura praeputialis Chordata E Competition Single-Species Competition Enhanced (Caro et al 2011) Pyura praeputialis Chordata E Competition Single-Species Competition Enhanced (Castilla et al 2004) Pyura praeputialis Chordata E Consumption Predation Limited (Castilla et al 2004) Salmo trutta Chordata O Competition Single-Species Competition Enhanced (Hasegawa & Maekawa 2008) Salmo trutta Chordata E Competition Single-Species Competition Enhanced (Hasegawa & Maekawa 2009) Sphyraena chrysotaenia Chordata O Competition Single-Species Competition Enhanced (Kalogirou et al 2012) Styela canopus Chordata E Consumption Predation Limited (Freestone et al 2013) Styela clava Chordata E Consumption Predation Enhanced (Freestone et al 2013) Acabaria erythraea Cnidaria O Competition Single-Species Competition Enhanced (Fine et al 2005) Chromonephthea braziliensis Cnidaria E Consumption Herbivory (allelopathy) Enhanced (Fleury et al 2008) Mnemiopsis leidyi Cnidaria O Consumption Predation Limited (Finenko et al 2001) Mnemiopsis leidyi Cnidaria E Consumption Predation Limited (Finenko et al 2003) Mnemiopsis leidyi Cnidaria O Competition Single-Species Competition Enhanced (Shiganova 1998 Enhanced/Limited (Kimbro et al 2013)…”
Section: Hemigrapsus Sanguineusmentioning
confidence: 99%
“…Rome and Ellis (2004) have found that the gut content of gulls, such as great black-backed gulls (Larus marinus) and herring gulls (L. argentatus), contain limbs of crabs with no associated carapace, though sublethal bird predation may be more important for the larger and more conspicuous native crabs of New England than for C. maenas and H. sanguineus (Lohrer 2001;Rome and Ellis 2004;Ellis et al 2007). Fish can also inflict limb loss on crabs, and limbs without the accompanying carapace have been documented in the guts of the common mummichog (Fundulus heteroclitus) and the striped killifish (F. majalis) (Brousseau et al 2008). Finally, local conditions, which we did not record (e.g., water temperature) could also be important in understanding the incidence of injury.…”
Section: Factors Affecting Crab Injurymentioning
confidence: 99%